Seismic retrofit of RC building structures with Buckling Restrained Braces. (1st January 2017) - Almeida, André; Ferreira, Ricardo; Proença, Jorge M.; Gago, António S.
Highlights: Development of design method proposed by Kasai et al. for BRB design. Optimization of BRB performance when located at different storeys of a building. Structural assessment through non-linear static and dynamic numerical analyses. Applicability study of developed method on a RC pre-code school building structure. Abstract: The search for passive control systems has increased in some high seismicity areas of the world, especially in terms of the strengthening of existing RC or steel building structures designed without earthquake-resistance considerations (pre-code structures) or with outdated structural codes. One of the most promising techniques consists of adding steel Buckling Restrained Braces (BRBs) to the existing structure. This paper presents an applicability study of these devices in the retrofit of a typical existing RC pre-code school building structure. The effectiveness of the retrofit solution, initially designed according to Kasai et al. (1998) formulation, was assessed through non-linear static and dynamic numerical analyses. The results of these analyses, led to the design method being developed with the purpose of optimising the dimensions of the steel dampers at different storeys and therefore improving the structural performance. This development is based on a simplified method of predicting the response of a passive system, by devising a single degree of freedom system. The effectiveness of the seismic retrofit solution designed through the improved design procedure was confirmed, showing that the studied strengthening solution results in a significant increase in strength, deformation and energy dissipation capacity, thereby limiting damage in the original structure to admissible levels.